MATLAB GUI Application for Processing the Remote Sensing Images - Andriani Putri; Shou-Hao Chiang; Abdurrahman Ridho (Jurnal Teknologi Informasi, 2023)
Spatial Data Analyst is important for image processing and accuracy assessment. To adjust a better image, we need to do some processes and steps in order to achieve this goal. MATLAB has been commonly used in image processing. MATLAB provides a Graphical Use Interface (GUI) designer "Guide" that is easy to use and does not require any programming experience. In this research, accuracy assessment, and image processing tools are built using MATLAB GUI. This straightforward GUI will also contain a Correlation Coefficient and Composite Band part. GUI is easier and more convenient for running the MATLAB functions and getting the results.